Thermodynamics of the Point Defects in the Metallic Phase of the Samarium Monosulphide - Gorichok, I.; Shevchuk, M.; Boychuk, V. (Journal of Vasyl Stefanyk Precarpathian National University, 2016)
The equilibrial values of the vacancy concentration of chalcogen and antistructural samarium atoms in metallic phase of SmS were calculated by minimization the crystal thermodynamic potential. It was determined that the dominant defects are